Method for producing electrode for secondary battery and wet powder

By granulating using wet powder composed of condensed particles of electrode active substances, carbon nanotubes and nonaqueous electrolytes, the problems of reduced battery performance and increased production costs caused by binder resins and solvents in the prior art are solved, and the electrode density and production costs are improved.

CN115207287BActive Publication Date: 2025-05-02PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210323754.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-01
Filing Date
2022-03-30
Publication Date
2025-05-02
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

Prior Art When manufacturing a nonaqueous electrolyte secondary battery, the adhesive resin and solvent used may lead to reduced battery performance and increase production costs.

Method used

The wet powder composed of condensed particles of electrode active substances, carbon nanotubes and nonaqueous electrolytes are used for granulation to form an electrode active substance layer, and the use of binder resins and solvents are avoided.

Benefits of technology

The electrode density is improved, the drying process and solvent recovery device are avoided, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115207287B_ABST
    Figure CN115207287B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing an electrode with improved electrode density while suppressing production costs. The electrode manufacturing method disclosed herein is a method for manufacturing an electrode having an electrode collector and an electrode active material layer of either a positive electrode or a negative electrode, comprising: a step of granulating a wet powder formed of agglomerated particles containing at least an electrode active material, carbon nanotubes, and a non-aqueous electrolyte; and a step of supplying the electrode active material layer composed of the wet powder to the electrode collector to form an electrode. The granulation step includes: a first mixing process of mixing the carbon nanotubes with the non-aqueous electrolyte so that the non-aqueous electrolyte is impregnated in the carbon nanotubes; a second mixing process of mixing the carbon nanotubes impregnated with the non-aqueous electrolyte with the electrode active material; and a process of compressing the mixture obtained by the first and second mixing processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an electrode for a secondary battery and a wet powder. Background Art

[0002] Compared with existing batteries, secondary batteries such as lithium-ion secondary batteries are lightweight and have high energy density, and therefore are preferably used as high-output power supplies for vehicle installation, or power supplies for personal computers and portable terminals. In particular, lithium-ion secondary batteries are preferably used as high-output power supplies for driving vehicles such as electric vehicles (BEV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV).

[0003] As a typical structure of the positive electrode and the negative electrode (hereinafter referred to as "electrode" without distinguishing between the positive and negative electrodes) of such a secondary battery, there can be cited a structure in which an electrode active material layer having an electrode active material as the main component is formed on one or both sides of a foil-shaped electrode collector. The electrode active material layer is prepared by dispersing solid components such as electrode active material, binding material (adhesive), and conductive material in a specified solvent to prepare a slurry (paste) electrode material, and applying the prepared slurry (paste) electrode material on the surface of the collector to form a coating film, and after the coating film is dried, a pressing pressure is applied to form a specified density and thickness. Alternatively, a wet powder film forming (Moisture Powder Sheeting: MPS) in which a so-called wet powder (Moisture Powder) with a higher proportion of solid components than the composite slurry and a granular aggregate is formed in a state where the solvent is retained on the surface of the active material particles and the surface of the binder molecules is used to form a film is also studied instead of such film forming using composite slurry. For example, Patent Documents 1 and 2 describe methods of forming an active material layer using wet powder.

[0004] Patent document 1 discloses a method for wet powder film formation by adjusting the contact angle of the electrode active material using a mixed solution of a solvent and a surfactant to form an electrode active material layer with uniform thickness on a collector foil. In addition, patent document 2 discloses a method for manufacturing a secondary battery, which includes the step of manufacturing granules containing a part of the solvent component of the electrolyte in order to suppress the reduction of battery performance and improve the ductility of the granules.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-113113

[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-117582 Summary of the invention

[0009] However, if it is considered from the viewpoint of improving electrode density, it is preferred to not contain non-conductive binder resins that may become resistance components as much as possible. In addition, the solvent used in the manufacture of such non-aqueous electrolyte secondary batteries in the past, as described in Patent Document 2, may reduce battery performance when it remains in the electrode and is brought into the battery. Therefore, in order to remove the solvent, it is necessary to implement a drying process and have a device for recovering the solvent, which increases production costs. Therefore, from the viewpoint of improving battery performance and increasing productivity, it is preferred that the non-conductive binder resins and solvents suitable for the manufacture of non-aqueous electrolyte secondary batteries are as little as possible (if you have to say, substantially free of).

[0010] The present invention has been made in view of the above circumstances, and its main object is to provide a method for producing an electrode with improved electrode density while suppressing production costs. Another object is to provide a wet powder that can appropriately produce the electrode.

[0011] In order to achieve the above-mentioned purpose, a method for manufacturing an electrode disclosed herein is provided. The manufacturing method disclosed herein is a method for manufacturing an electrode having an electrode collector and an electrode active material layer of either a positive electrode or a negative electrode, and includes the following steps: a step of granulating a wet powder formed by agglomerated particles containing at least an electrode active material, a carbon nanotube, and a non-aqueous electrolyte; a step of supplying the electrode active material layer composed of the wet powder to the electrode collector to form an electrode. The granulation step includes: a first mixing process of mixing the carbon nanotubes with the non-aqueous electrolyte so that the non-aqueous electrolyte is impregnated in the carbon nanotubes; a second mixing process of mixing the carbon nanotubes impregnated with the non-aqueous electrolyte with the electrode active material; and a process of compressing the mixture obtained by the first and second mixing processes.

[0012] As described above, after the non-aqueous electrolyte is impregnated into the carbon nanotubes in the first mixing process, it is mixed with the electrode active material in the second mixing process, thereby preferentially allowing the non-aqueous electrolyte to adhere to the surface of the electrode active material. Next, the electrode active materials with non-aqueous electrolyte attached to the surface are granulated as wet powders in a state where they are appropriately combined by liquid cross-linking forces. By using the wet powder in this state, an electrode active material layer can be formed on the electrode collector even in a manner that does not substantially contain a binder resin and a solvent. Since the wet powder does not use the non-conductive binder resin used in the previous method for manufacturing secondary batteries, or a solvent that is concerned about adversely affecting battery performance, the electrode density is improved and a drying process and a solvent recovery device for removing the solvent are not required. Therefore, according to this structure, it is possible to manufacture an electrode with an improved electrode density while suppressing production costs.

[0013] In a preferred embodiment of the manufacturing method disclosed herein, for the wet powder granulated in the granulation step, in the agglomerated particles, the solid phase and the liquid phase form a capillary state, and when the wet powder as a whole is set to 100 mass%, the solid content is 70 mass% or more.

[0014] The wet powder forms a capillary state described later in the solid phase and the liquid phase in the agglomerated particles constituting the wet powder, thereby being able to more appropriately form an electrode active material layer on the electrode current collector. In order to appropriately form such a capillary state, the solid content of the wet powder is preferably 70% by mass or more. According to this constitution, an electrode active material layer can be formed even in a manner that does not substantially contain a binder resin.

[0015] In a preferred embodiment of the production method disclosed herein, the carbon nanotubes have an oil absorption of 280 mL / 100 g to 1000 mL / 100 g.

[0016] According to this configuration, by using carbon nanotubes having a certain amount of oil absorption, the nonaqueous electrolyte can be better impregnated into the carbon nanotubes in the first mixing step. Thus, in the granulation step, wet powder that fully exerts the crosslinking force of the liquid can be granulated.

[0017] In a preferred embodiment of the manufacturing method disclosed herein, the electrode forming step is performed by making the wet powder supplied between the first roller and the second roller adhere to the outer peripheral surface of the second roller as the electrode active material layer, and transferring the electrode active material layer from the outer peripheral surface of the second roller to the surface of the electrode collector supplied separately to the second roller, thereby forming the electrode, wherein the second roller is arranged opposite to the first roller.

[0018] According to this configuration, the electrode active material layer composed of the wet powder can be formed more efficiently on the electrode current collector.

[0019] In order to achieve the above other purposes, a wet powder disclosed herein is provided. The wet powder disclosed herein is a wet powder for forming an electrode active material layer on an electrode current collector of either a positive electrode or a negative electrode, and is composed of agglomerated particles containing an electrode active material, carbon nanotubes, and a non-aqueous electrolyte. When the wet powder as a whole is set to 100% by mass, the solid content is 70% by mass or more. In the above-mentioned agglomerated particles, the solid phase and the liquid phase form a capillary state. The oil absorption of the above-mentioned carbon nanotubes is 280mL / 100g to 1000mL / 100g.

[0020] According to this configuration, it is possible to provide a wet powder capable of appropriately producing an electrode having an improved electrode density. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flowchart showing a schematic process of an electrode manufacturing method according to one embodiment.

[0022] Figure 2 This is a flow chart showing a granulation step according to one embodiment.

[0023] Figure 3 The diagrams schematically show the existence forms of the solid phase (solid components such as active material particles), liquid phase (solvent), and gas phase (voids) of the agglomerated particles constituting wet powders. (A) shows a pendular state, (B) shows a funicular state, (C) shows a capillary state, and (D) shows a slurry state.

[0024] Figure 4 This is a diagram schematically showing a wet powder obtained in a granulation step according to one embodiment.

[0025] Figure 5 It is an explanatory diagram schematically showing the structure of a roll film forming apparatus according to one embodiment.

[0026] Figure 6 It is an explanatory diagram schematically showing a lithium ion secondary battery according to one embodiment.

[0027] Explanation of symbols

[0028] 1 Agglomerated particles

[0029] 2 Solid components (solid phase)

[0030] 3 Liquid components (liquid phase)

[0031] 4 Void (gas phase)

[0032] 20 Wet powder

[0033] 22 Electrode active material

[0034] 24 Non-aqueous electrolyte

[0035] 26 Carbon Nanotubes

[0036] 31. Electrode collector

[0037] 32 Electrode active material layer

[0038] 40 roll film forming device

[0039] 41 First rotating roller (supply roller)

[0040] 42 Second rotating roller (transfer roller)

[0041] 43 Support roller

[0042] 45 Next Door

[0043] 50 Battery housing

[0044] 52 Positive terminal

[0045] 52a Positive electrode collector plate

[0046] 54 Negative terminal

[0047] 54a Negative collector plate

[0048] 56 Safety valve

[0049] 60 positive electrode

[0050] 62 positive electrode collector

[0051] 64 Positive electrode active material layer

[0052] 66 Positive electrode active material layer non-forming portion

[0053] 70 negative electrode

[0054] 72 negative electrode collector

[0055] 74 Negative electrode active material layer

[0056] 76 Negative electrode active material layer non-forming portion

[0057] 80 Wound electrode body

[0058] 90 Isolation

[0059] 100 Lithium-ion secondary battery DETAILED DESCRIPTION

[0060] Hereinafter, the method for producing the electrode disclosed herein and the wet powder that can be used to produce the electrode will be described in detail by taking an electrode that can be suitably used in a lithium ion secondary battery as a typical example of a secondary battery as an example.

[0061] Matters other than those not specifically mentioned in this specification and required for implementation can be understood as design matters for those skilled in the art based on the prior art in the field. The technical contents disclosed here can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0062] In addition, the dimensional relationship (length, width, height, etc.) does not reflect the actual dimensional relationship.

[0063] In addition, in this specification, the expression "A to B (wherein A and B are arbitrary values)" which shows a range means A or more and B or less.

[0064] In this specification, "secondary battery" refers to a general battery that can be recharged repeatedly. In addition, "non-aqueous electrolyte secondary battery" refers to a battery having a non-aqueous electrolyte (typically, a non-aqueous electrolyte containing a supporting electrolyte in a non-aqueous solvent). "Lithium-ion secondary battery" refers to a secondary battery that uses lithium ions as charge carriers and achieves charging and discharging by the movement of charges accompanying lithium ions between positive and negative electrodes. In addition, in this specification, when there is no need to specifically distinguish between the positive and negative electrodes, they are simply referred to as electrodes.

[0065] Figure 1 1 is a flowchart showing a method for manufacturing a non-aqueous electrolyte secondary battery disclosed herein. The method for manufacturing an electrode disclosed herein includes: a step of granulating a wet powder formed by agglomerated particles containing at least an electrode active material, carbon nanotubes and a non-aqueous electrolyte (S110), and a step of supplying an electrode active material layer composed of the wet powder to the electrode current collector to form an electrode (S120). Each step is described in detail below.

[0066] <Granulation process>

[0067] like Figure 2 As shown, the granulation process S110 includes: a first mixing treatment (S112) of mixing carbon nanotubes with a non-aqueous electrolyte, a second mixing treatment (S114) of further adding an electrode active material for mixing after the first mixing treatment, and a compression treatment (S116) of compressing the mixture obtained by the first and second mixing treatments.

[0068] The wet powder granulated in the manufacturing method disclosed herein is typically composed of agglomerated particles containing an electrode active material, carbon nanotubes, and a non-aqueous electrolyte. The wet powder is in a powdery state as a whole and is in a state of a free liquid surface without a gas-liquid interface. As a powder showing such properties, for example, it is preferred that the agglomerated particles constituting the wet powder form a capillary state described later. By forming the capillary state with the wet powder, the wet powders are integrated with each other and stretched to appropriately form a film-like electrode active material layer.

[0069] Regarding the morphological classification of the wet powder, the present specification also adopts the four types of classification described in "Particle Size Enlargement" by Capes CE (published by Elsevier Scientific Publishing Company, 1980) and which are currently well known, and the wet powder disclosed here is clearly defined. Specifically, it is as follows.

[0070] The existence forms (filling states) of the solid phase (solid components such as active material particles), liquid phase (liquid components such as non-aqueous electrolyte) and gas phase (voids) of the agglomerated particles that constitute the wet powder can be classified into four types: "pendulum state", "ribbon state", "capillary state" and "mud state".

[0071] like Figure 3 As shown in (A), the "pendulum state" is a state in which the liquid component (liquid phase) 3 exists discontinuously in a manner that cross-links the solid components (solid phase) 2 in the condensed particles 1, and the solid components 2 can exist in a mutually connected (continuous) state. As shown in the figure, the content of the liquid component 3 is relatively low, and as a result, the voids (gas phase) 4 present in the condensed particles 1 mostly exist continuously, forming a connecting hole leading to the outside.

[0072] In addition, if Figure 3 As shown in (B), the "cord state" is a state in which the content of the liquid component 3 in the condensed particle 1 is relatively high compared to the pendulum, and the liquid component 3 is continuously present around the solid component 2 in the condensed particle 1. However, the amount of the liquid component 3 is still small, so the solid component 2 exists in a mutually connected (continuous) state as in the pendulum state. Although there is a trend that the proportion of connected holes leading to the outside in the voids 4 existing in the condensed particle 1 is slightly reduced, and the proportion of discontinuous isolated voids is increased, the existence of connected holes is confirmed.

[0073] like Figure 3 As shown in (C), the "capillary state" is when the content of the liquid component 3 in the condensed particle 1 increases, and the amount of the liquid component 3 in the condensed particle 1 is close to the saturated state. A sufficient amount of the liquid component 3 exists continuously around the solid component 2, and as a result, the solid component 2 exists in a discontinuous state. The solid components are filled with the liquid component 3, and the binding force between the solid components is strong. By the liquid component 3 staying on the surface of the condensed particle 1, the surface of the condensed particle 1 is in a wet state, and becomes a state in which viscosity can be exerted. By increasing the content of the liquid component 3 in the condensed particle 1, there are almost no voids. When there are voids, almost all of them (for example, more than 80 vol% of the total void volume) exist in the form of isolated voids.

[0074] like Figure 3 As shown in (D), the "slurry state" is a state in which the solid component 2 is suspended in the liquid component 3, and is a state that cannot be called aggregated particles. Compared with the capillary state, there is no gas phase.

[0075] The solid content of the wet powder can be any solid content at which the wet powder properly realizes the above-mentioned capillary state, and is typically 70% by mass or more when the total mass of the wet powder is 100% by mass. A certain amount of liquid component 3 is required for the wet powder to form an appropriate capillary state, so the solid content may be 87% by mass or less, 85% by mass or less, or 83% by mass or less.

[0076] In addition, the "solid content ratio" in this specification refers to the ratio of the solid content in the whole wet powder.

[0077] As the main component of the solid component 2, i.e., the electrode active material, a compound having a composition used as a negative electrode active material or a positive electrode active material of a conventional secondary battery (here, a lithium ion secondary battery) can be used. For example, carbon materials such as graphite, hard carbon, and soft carbon can be cited as negative electrode active materials. In addition, as other examples of negative electrode active materials, metal materials composed of metals such as tin (Sn), aluminum (Al), zinc (Zn), silicon (Si), or alloys with these metals as the main body (so-called alloy-based negative electrodes) can be cited. As positive electrode active materials, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 Lithium transition metal composite oxides such as O4, lithium transition metal phosphate compounds such as LiFePO4. The average particle size of the electrode active material is not particularly limited, but is appropriately about 0.1 μm to 50 μm, preferably about 1 to 20 μm.

[0078] It should be noted that in this specification, the "average particle size" refers to the particle size (D) corresponding to 50% by volume of the cumulative frequency from the side of the particles with smaller particle sizes in the volume-based particle size distribution based on the general laser diffraction / light scattering method. 50 , also called median particle size).

[0079] The oil absorption of the carbon nanotubes contained in the wet powder is required to be 280 mL / 100 g to 1000 mL / 100 g. By using carbon nanotubes having an oil absorption within this range, the non-aqueous electrolyte can be properly maintained in the first mixing process S112 described later, and when mixed with the electrode active material in the second mixing process S114, the non-aqueous electrolyte is preferentially applied to the surface of the electrode active material.

[0080] The oil absorption of the carbon nanotubes can be measured using dibutyl phthalate (DBP) as a reagent liquid according to the method described in JIS K6217-4:2008.

[0081] As carbon nanotubes, it can be a single-layer carbon nanotube (SWNT) composed of a cylindrical graphene sheet, it can also be a two-layer carbon nanotube (DWNT) in which two different SWNTs become nested, and it can also be a multi-layer carbon nanotube (MWNT) in which three or more different SWNTs become nested. From the viewpoint of appropriately satisfying the above-mentioned oil absorption, it is preferably a carbon nanotube with more than 2 layers (DWNT, MWNT). They can be used alone or in combination of more than 2. Carbon nanotubes can be manufactured by arc discharge method, laser ablation method, chemical vapor growth method, etc.

[0082] The average length of the carbon nanotubes is not particularly limited as long as it has the oil absorption as described above. By having a certain average length, it can contribute to the improvement of the bonding between the electrode active materials and the conductive path. The average length of the carbon nanotubes is, for example, preferably more than 5 μm, can be more than 8 μm, and can also be more than 10 μm. When the average length is too long, the carbon nanotubes may become excessively condensed during mixing. The average length of the carbon nanotubes can typically be less than 150 μm, for example, less than 120 μm. By using carbon nanotubes with an average length in this range, the carbon nanotubes are appropriately entangled with the electrode active material, and the bonding between the electrode active materials and the conductive path can be appropriately ensured.

[0083] The average diameter of the carbon nanotubes is not particularly limited, and may be, for example, 2 nm to 150 nm, or 5 nm to 120 nm. The average length and average diameter of the carbon nanotubes may be values ​​obtained by, for example, electron microscopic observation.

[0084] The aspect ratio (average length / average diameter) of the carbon nanotubes is typically preferably 100 or more. The larger the aspect ratio of the carbon nanotubes, the easier it is to entangle, and therefore, the function of the binder and the conductive material can be fully exerted between the electrode active materials. The aspect ratio can be more than 250, more than 500, or more than 800. From the perspective of dispersibility in the granulation process, the aspect ratio is appropriately about 25,000 or less, preferably 20,000 or less, and more preferably 15,000 or less.

[0085] As the non-aqueous electrolyte used in the wet powder, the same non-aqueous electrolyte as that used in the previous secondary battery can be used. Typically, a non-aqueous electrolyte containing a supporting electrolyte (also called a supporting salt) in a non-aqueous solvent can be used. As the non-aqueous solvent, carbonates, esters, ethers, nitriles, sulfones, lactones and other non-aqueous solvents can be used without particular limitation. Specifically, for example, non-aqueous solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC) can be preferably used. Such non-aqueous solvents can be used alone or in combination of two or more.

[0086] As the supporting salt contained in the non-aqueous solvent, the supporting salt used in the non-aqueous electrolyte secondary battery in the past can be used without particular limitation. For example, lithium salts such as LiPF6, LiBF4, LiAsF6, LiCF3SO3, LiC4F9SO3, LiN(CF3SO2)2, and LiC(CF3SO2)3 can be used.

[0087] Although not particularly limited, in the manufacturing method disclosed herein, the supporting salt concentration in the non-aqueous electrolyte in the granulation step S110 can be set higher than before. For example, it can be 2mol / L to 5mol / L, or it can be 2.5mol / L to 4.5mol / L. As long as the concentration of the supporting salt of the non-aqueous electrolyte when the non-aqueous electrolyte secondary battery is constructed to be approximately 1mol / L (e.g., 0.7mol / L to 1.3mol / L), it can be appropriately adjusted in the injection process of the non-aqueous electrolyte generally implemented in such a manufacturing method in the past.

[0088] The nonaqueous electrolyte of the nonaqueous secondary battery of this embodiment may contain various additives such as a gas generating agent such as biphenyl (BP) and cyclohexylbenzene (CHB); a film forming agent; a dispersant; and a thickener, as long as the effects of the present invention are not significantly impaired.

[0089] From the viewpoint of energy density, the proportion of electrode active material in the solid content of the wet powder as a whole can be roughly 70 to 99.5% by mass, typically 80 to 99% by mass, for example 85 to 95% by mass. In addition, the proportion of carbon nanotubes in the solid content of the wet powder as a whole can be typically 0.5 to 20% by mass, for example 1 to 10% by mass. In addition, as long as the effect of the present invention is not impaired, the wet powder may also contain materials other than the above (such as various additives, etc.). In the case of containing various additives, the proportion of additives in the solid content of the wet powder as a whole is preferably less than 7% by mass, more preferably less than 5% by mass. It should be noted that the wet powder does not contain a liquid dispersion medium that can disperse the powdery material and improve fluidity.

[0090] like Figure 2 As shown, the granulation process disclosed herein includes: a first mixing treatment S112 of mixing carbon nanotubes with a non-aqueous electrolyte, a second mixing treatment S114 of mixing the mixture of the electrolyte and the carbon nanotubes with an electrode active material, and a compression treatment S116 of compressing the mixture obtained by the first and second mixing treatments. The mixing method can be mixed by a conventionally known method. As a method for making granulated particles, for example, granulation methods such as a tumbling granulation method, a fluidized bed granulation method, a stirring granulation method, a compression granulation method, an extrusion granulation method, a crushing granulation method, and a spray drying method can be cited. Among them, the compression granulation method can appropriately granulate the wet powder disclosed herein, and is therefore preferred.

[0091] In the first mixing process S112, the carbon nanotubes and the non-aqueous electrolyte are mixed using a conventionally known mixing device. As the mixing device, for example, a planetary mixer or other agitator can be used for mixing. The agitator typically comprises: a cylindrical mixing container, a rotating blade accommodated in the mixing container, and a motor connected to the rotating blade via a rotating shaft.

[0092] The carbon nanotubes and the non-aqueous electrolyte are added to the mixing container of the mixer and mixed so that the non-aqueous electrolyte is fully impregnated in the carbon nanotubes. The mixing time of the first mixing treatment may vary depending on the device configuration, etc., and is generally about 1 to 60 seconds (e.g., 2 to 40 seconds). In addition, the rotation speed may be, for example, about 2000 rpm to 5000 rpm. By mixing under this mixing condition, a mixture in which the carbon nanotubes are moderately agglomerated and the non-aqueous electrolyte is maintained can be obtained.

[0093] The non-aqueous electrolyte is measured and added in such a way that the solid content of the wet powder becomes 70% by mass or more. The wet powder disclosed here has a solid content set to a relatively high value compared to the conventional slurry composition. By making the solid content a relatively high value, the electrode active material, the carbon nanotubes and the non-aqueous electrolyte can be properly integrated and granulated into the above-mentioned capillary state. If the granulated particles are in the capillary state, it is easy to improve the adhesion of each granulated particle to each other in the electrode forming step S120, and film formation can be properly performed.

[0094] In the second mixing process S114, the carbon nanotubes impregnated with the non-aqueous electrolyte obtained by the first mixing process S112 are mixed with the electrode active material. The electrode active material can be put into all of the prepared active material at one time, or a small amount can be put in each time. The first mixing process S112 and the second mixing process S114 can be carried out using the same mixing device, or different mixing devices, but from the perspective of productivity, it is preferred to use the same mixing device. For example, the electrode active material can be further put into the mixing container of the stirrer used in the first mixing process S112 for mixing. The mixing time of the second mixing process S114 is preferably set to be shorter than the mixing time of the first mixing process S112. For example, it can be about 1 to 30 seconds. In addition, the rotation speed of the second mixing process S114 can be a rotation speed smaller than the rotation speed of the first mixing process, for example, it can be about 100rpm to 1000rpm.

[0095] In the compression process S116, the mixture obtained by the first and second mixing processes is compressed and granulated using a conventionally known granulator. For example, as a preferred embodiment of the granulator, a roller mill that compresses and granulates by inserting the mixture between a pair of rollers rotating in opposite directions can be cited.

[0096] In the compression granulation performed by a roller mill, the mixture (carbon nanotubes impregnated with a non-aqueous electrolyte and an electrode active material) is granulated while applying a high compression force and a shearing force. Although not particularly limited, it is presumed that the granulation method described below can appropriately form a wet powder in a capillary state.

[0097] The carbon nanotubes impregnated with the non-aqueous electrolyte and the electrode active material are compressed and rubbed against each other, so that the impregnated non-aqueous electrolyte is squeezed out of the carbon nanotubes and forms agglomerated particles while preferentially adhering to the surface of the electrode active material. In addition, the gas is squeezed out of the mixture and the gaps between the electrode active materials become smaller, resulting in a state where the density of the active material is high. That is, the solid component 2 (here, the electrode active material) and the liquid component 3 (here, the non-aqueous electrolyte) can form a Figure 3(C) shows a capillary aggregated particle 1. The carbon nanotubes squeezed out of the non-aqueous electrolyte are crushed by the high compressive force and are drawn into the formed aggregated particles, adhering to the surface of the aggregated particles.

[0098] According to the view of the inventor, it is found that when the electrode active material, carbon nanotubes and non-aqueous electrolyte are all mixed at the same time and granulated by compression granulation, the cohesive strength of the formed granules (wet powder) is low. Although it is not intended to limit the technology disclosed herein, the reason for the above effect can be inferred as follows. For example, when all materials are put into the same time and mixed, each component is evenly dispersed. It is inferred that in this case, the non-aqueous electrolyte will not be preferentially configured on the surface of the electrode active material, and the liquid cross-linking force (the sum of capillary negative pressure and surface tension) between the electrode active materials decreases.

[0099] Figure 4 An example of the wet powder 20 formed in the granulation step S110 is schematically shown. Figure 4 As shown, it contains at least a plurality of electrode active materials 22, a non-aqueous electrolyte 24 and carbon nanotubes 26. In a preferred embodiment, in the agglomerated particles constituting the wet powder 20, the solid phase and the liquid phase form the above-mentioned capillary state, and a sufficient amount of non-aqueous electrolyte 24 continuously exists around the electrode active material 22. As a result, the electrode active material 22 exists in a discontinuous state. Moreover, carbon nanotubes 26 are attached to the surface of the above-mentioned agglomerated particles. Although not particularly limited, the carbon nanotubes 26 are preferably not uniformly dispersed in the wet powder 20, but are biased around the electrode active material 22. As a result, the carbon nanotubes 26 can contribute to the bonding of the electrode active materials 22 to each other and the improvement of the conductive path between the active materials.

[0100] The wet powder 20 granulated by the granulation step S110 of the manufacturing method disclosed herein does not substantially contain the binder resin used in the previous electrode manufacturing method. The so-called binder resin here refers to a substance that acts as a binder and does not have conductivity. As an example, rubbers such as styrene butadiene copolymer (SBR), acrylic modified SBR resin (SBR latex), cellulose polymers such as carboxymethyl cellulose (CMC), acrylic resins such as methacrylate polymers, polyvinylidene fluoride (PVdF), etc. can be cited.

[0101] In this specification, “substantially free of” means that the target component is not intentionally added, that the component is not contained at all, or that the production method disclosed herein contains only a very small amount (so-called contamination level) of an insignificant degree.

[0102] In the previous method for manufacturing wet powders, the wet powder is granulated by a stirring granulation method in which solid components (such as electrode active materials, binder resins, conductive materials, etc.) are pre-mixed by a dry mixing method and a small amount of solvent (liquid component) is added for further mixing. In this stirring granulation method, the solid components collide with each other while rotating irregularly due to the rotation of the blade, and gradually granulate into large blocks (granules) while agglomerating. At this time, the binder resin contained in the solid components plays a role in bonding the agglomerated solid components to each other. Therefore, in the above-mentioned stirring granulation method, the binder resin is an essential component. However, the binder resin can generally become a resistance component when it is constructed into an electrode, so it is preferably as little as possible (if it is necessary to say, substantially not contain it).

[0103] In contrast, in the granulation step S110 disclosed herein, the carbon nanotubes 26 having the above-mentioned characteristics are firstly impregnated with the non-aqueous electrolyte 24 by the first mixing process S112 in which the carbon nanotubes 26 are mixed with the non-aqueous electrolyte 24. Thereafter, the carbon nanotubes 26 impregnated with the non-aqueous electrolyte 24 are mixed with the electrode active material 22 by the second mixing process S114. By the compression process S116 in which the mixture obtained by the first mixing process S112 and the second mixing process S114 is compressed, the non-aqueous electrolyte 24 is preferentially arranged on the surface of the electrode active material 22, and the above-mentioned capillary state aggregated particles are appropriately formed. Furthermore, the carbon nanotubes 26 that are appropriately crushed by compression are further arranged on the surface of the above-mentioned aggregated particles, thereby forming the wet powder 20 in which the bonding force and the conductive path of the electrode active material 22 are improved. Thus, the wet powder 20 can be granulated even in a mode that substantially does not contain a binder resin that can become a resistor component.

[0104] In addition, the wet powder 20 granulated by the granulation step S110 disclosed here does not substantially contain the solvent used in the previous electrode manufacturing method. The so-called solvent here is a liquid component that is concerned about adversely affecting the battery performance when it is constructed into a secondary battery. As an example, N-methyl-2-pyrrolidone (NMP), an aqueous solvent (water or a mixed solvent with water as the main body), etc. can be cited. The above-mentioned solvent is used as an essential component in the previous manufacturing method for the purpose of properly dispersing active materials, conductive materials, etc. However, if the solvent remains when constructing the electrode, it will have an adverse effect on the battery performance, so it is necessary to remove the solvent by drying, etc. In contrast, the wet powder disclosed here does not substantially contain the previous solvent, and a non-aqueous electrolyte is used that does not adversely affect the battery performance when it is constructed into a secondary battery. Therefore, there is no need to have a solvent removal process or a solvent recovery device, which can suppress production costs.

[0105] The average particle size of the wet powder 20 granulated in the granulation step S110 may be approximately 10 μm or more, 100 μm or more, or 1 mm or more. The upper limit of the average particle size is not particularly limited, but may be typically 10 mm or less, for example 5 mm or less.

[0106] <Electrode formation process>

[0107] The electrode forming step S120 is a step of forming an electrode by supplying an electrode active material layer composed of the wet powder granulated in the granulation step S110 onto an electrode current collector. The electrode active material layer 32 composed of the wet powder 20 can be formed using the schematic diagram shown in FIG. Figure 5 Such a roll film forming device 40 is performed. As shown in the drawings, the roll film forming device 40 includes: a first rotating roller 41 (hereinafter also referred to as "supply roller 41") and a second rotating roller 42 (hereinafter also referred to as "transfer roller 42") arranged opposite to the first rotating roller 41. The outer peripheral surface of the supply roller 41 and the outer peripheral surface of the transfer roller 42 are opposite to each other. The pair of rotating rollers 41 and 42 are as shown in FIG. Figure 5 As shown by the arrow, the supply roller 41 and the transfer roller 42 can rotate in opposite directions. In addition, the gap between the supply roller 41 and the transfer roller 42 can be separated by only a distance corresponding to the desired thickness of the electrode active material layer 32 formed on the long sheet-shaped electrode collector 31. In addition, by adjusting the size of the gap, it is also possible to adjust the force that compresses the wet powder 20 passing between the supply roller 41 and the transfer roller 42. Therefore, by adjusting the size of the gap between the supply roller 41 and the transfer roller 42 according to the solid content rate of the wet powder 20, etc., the granulated particles are appropriately integrated with each other, stretched and formed into a film.

[0108] The electrode collector 31 can use a metal electrode collector used as an electrode collector of this secondary battery without particular limitation. When the electrode collector 31 is a positive electrode collector, for example, it is composed of a metal material with good electrical conductivity, such as aluminum, nickel, titanium, stainless steel, etc. Aluminum (such as aluminum foil) is particularly preferred. When the electrode collector 31 is a negative electrode collector, for example, it is composed of a metal material with good electrical conductivity, an alloy with copper as the main body, nickel, titanium, stainless steel, etc. Copper (such as copper foil) is particularly preferred. The thickness of the electrode collector 31 is, for example, approximately 5μm to 20μm, preferably 8μm to 15μm.

[0109] Partition walls 45 are provided at both ends in the width direction of the supply roller 41 and the transfer roller 42. The partition walls 45 play the following role: the wet powder 20 is held on the supply roller 41 and the transfer roller 42, and the width of the electrode active material layer 32 formed on the electrode collector 31 is defined by the distance between the two partition walls 45. The electrode material (wet powder 20) is supplied between the two partition walls 45 by a feeder (not shown) or the like.

[0110] In the roll film forming device 40 of this embodiment, a support roller 43 is arranged as a third rotating roller next to the transfer roller 42. The support roller 43 plays a role in conveying the electrode collector 31 to the transfer roller 42. The transfer roller 42 and the support roller 43 are as follows. Figure 5 The arrows rotate in opposite directions.

[0111] The supply roller 41, transfer roller 42 and support roller 43 are respectively connected to independent driving devices (motors) not shown in the figure. By gradually increasing the rotation speeds of the supply roller 41, transfer roller 42 and support roller 43 in this order, the wet powder 20 can be transported along the transfer roller 42 and transferred as the electrode active material layer 32 from the outer peripheral surface of the transfer roller 42 to the surface of the electrode collector 31 transported by the support roller 43.

[0112] Although not particularly limited, the size (width) of the gaps between the supply roller 41, the transfer roller 42, and the support roller 43 may be set to a gap size such that the average film thickness of the electrode active material layer 32 during film formation is 10 μm to 300 μm (e.g., 20 μm to 150 μm).

[0113] The sizes of the supply roller 41, the transfer roller 42, and the support roller 43 are not particularly limited, and can be the same as those of the conventional roller film forming apparatus, for example, the diameters can be 50 mm to 500 mm, respectively. The diameters of these supply rollers 41, the transfer roller 42, and the support roller 43 can be the same diameter or different diameters. In addition, the width of the electrode active material layer 32 can be appropriately determined according to the width of the electrode collector 31 on which the electrode active material layer 32 is to be formed, as in the conventional roller film forming apparatus. In addition, the material of the outer peripheral surface of the supply roller 41, the transfer roller 42, and the support roller 43 can be the same as that of the rotating roller in the conventionally known roller film forming apparatus, for example, SUS steel, SUJ steel, etc. can be cited.

[0114] It should be explained that Figure 5 In the embodiment, the supply roller 41, the transfer roller 42, and the support roller 43 are arranged so that their respective rotation axes are horizontally aligned, but the arrangement of the rollers is not limited to this.

[0115] In the electrode forming process S120 disclosed here, first, the wet powder 20 is supplied between a pair of supply rollers 41 and a transfer roller 42 rotating in opposite directions. The wet powder 20 is transported to the gap (gap) between the pair of rollers by the supply roller 41 and the transfer roller 42 rotating in opposite directions. Next, the wet powder 20 passes through the gap between the supply roller 41 and the transfer roller 42 while being compressed, and forms a film to form an electrode active material layer 32. That is, the wet powder 20 is compressed by the supply roller 41 and the transfer roller 42, and the wet powders 20 are integrated with each other and stretched to form a film-like electrode active material layer 32. At this time, the wet powders 20 are not particularly limited to each other (specifically, the agglomerated particles are each other), but it is presumed that they are combined by liquid cross-linking force. As the adhesion (binding force) between particles, in addition to the liquid cross-linking force, van der Waals force, electrostatic force, etc. can also be cited, but the liquid cross-linking force can exert a greater adhesion force, for example, when the solid content is 70% by mass or more (for example, 70 to 87% by mass), it can also exert appropriate adhesion. In addition, the carbon nanotubes 26 exist on the surface of the condensed particles, strengthening the binding force. Therefore, by compressing the wet powder 20 in the capillary state described above, a film-like electrode active material layer 32 can be formed even in a manner that does not substantially contain a binder resin.

[0116] Next, the electrode active material layer 32 is attached to the transfer roller 42 and transported. As described above, the rotation speed of the transfer roller 42 is set faster than that of the supply roller 41, so that the formed electrode active material layer 32 is attached to the transfer roller 42. The electrode active material layer 32 attached to the transfer roller 42 is transported by the rotation of the transfer roller 42 and is transferred to the electrode collector 31 supplied by the support roller 43. At this time, the electrode active material layer 32 contacts the electrode collector 31 with a certain degree of pressure, thereby transferring the electrode active material layer 32 to the electrode collector 31. As a result, an electrode having an electrode active material layer 32 on the electrode collector 31 can be obtained.

[0117] The electrode active material layer composed of a general slurry electrode material is formed by preparing an electrode active material and a binder into a slurry electrode material with an appropriate solvent, applying the obtained electrode material to a collector and drying it, and then pressing it. According to this method, when the slurry electrode material applied to the collector is dried, a phenomenon occurs in which the binder with a small specific gravity segregates on the surface side, that is, migration. If this migration occurs, the adhesion between the electrode collector and the electrode active material layer is reduced, and the active material layer is easily peeled off from the collector during the manufacturing process and repeated charging and discharging. In addition, the slurry electrode material has a low solid content rate (typically less than 55%) and takes time to remove the solvent based on drying, so there is also a problem of reduced productivity. In contrast, in the method for manufacturing an electrode disclosed here, since a non-aqueous electrolyte is used as a liquid component, it is not necessary to remove the liquid component. As a result, a high-quality electrode in which the electrode active material layer will not be peeled off from the electrode collector can be manufactured without migration. In addition, according to the above reasons, a solvent removal process and a solvent recovery device are not required, and an increase in productivity is also achieved. In addition, since a wet powder that does not substantially contain a binder resin that can become a resistor component after building a battery is used and the above-mentioned roller film forming device is used to compress and form a film, the density of the solid component (electrode active material) can be increased. As a result, the pressing process (process for adjusting the density of the electrode active material layer) in the previous manufacturing method is not required. Therefore, according to the manufacturing method of the electrode disclosed herein, it is possible to suppress the production cost and manufacture a higher quality electrode than before.

[0118] The sheet-shaped electrode thus produced is used as a normal sheet-shaped positive electrode or negative electrode of this type for construction of a secondary battery.

[0119] Figure 6 The lithium-ion secondary battery 100 shown is constructed by accommodating a flat-shaped wound electrode body 80 and a non-aqueous electrolyte (not shown) in a sealable box-shaped battery case 50. The battery case 50 is provided with a positive terminal 52 and a negative terminal 54 for external connection, and a thin-walled safety valve 56 set in a manner to release the internal pressure of the battery case 50 when the internal pressure rises to a predetermined level or above. In addition, the battery case 50 is provided with an injection port (not shown) for injecting a non-aqueous electrolyte or a non-aqueous solvent. The positive terminal 52 is electrically connected to the positive electrode collector plate 52a. The negative terminal 54 is electrically connected to the negative electrode collector plate 54a.

[0120] The wound electrode body 80 typically has a shape in which a long sheet-shaped positive electrode (hereinafter referred to as a positive electrode sheet 60) and a long sheet-shaped negative electrode (hereinafter referred to as a negative electrode sheet 70) are overlapped and wound in the long side direction via a long sheet-shaped separator 90. The positive electrode sheet 60 has a structure in which a positive electrode active material layer 64 is formed on one side or both sides of a positive electrode collector 62 along the long side direction. The negative electrode sheet 70 has a structure in which a negative electrode active material layer 74 is formed on one side or both sides of a negative electrode collector 72 along the long side direction. An edge portion on one side in the width direction of the positive electrode collector 62 is provided with a region (i.e., a positive electrode active material layer non-formed portion 66) along the edge portion where the positive electrode active material layer 64 is not formed and the positive electrode collector 62 is exposed. A region where the negative electrode active material layer 74 is not formed and the negative electrode current collector 72 is exposed (i.e., a negative electrode active material layer non-formed portion 76) is provided at the edge portion on the other side in the width direction of the negative electrode current collector 72. The positive electrode current collector plate 52a and the negative electrode current collector plate 54a are joined to the positive electrode active material layer non-formed portion 66 and the negative electrode active material layer non-formed portion 76, respectively.

[0121] The positive electrode (positive electrode sheet 60) and the negative electrode (negative electrode sheet 70) can use the positive electrode and negative electrode obtained by the above-mentioned manufacturing method. It should be noted that in this configuration example, the positive electrode and the negative electrode are formed by forming an electrode active material layer 32 (positive electrode active material layer 64 and negative electrode active material layer 74) on both sides of the electrode collector 31 (positive electrode collector 62 and negative electrode collector 72).

[0122] As the separator 90, for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator 90 can be provided with a heat-resistant layer (HRL).

[0123] The lithium ion secondary battery 100 constructed as above can be used for various purposes. As suitable uses, a driving power supply mounted on vehicles such as electric vehicles (BEV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV) can be cited. The lithium ion secondary battery 100 can also be used in the form of a battery pack formed by connecting a plurality of batteries in series and / or in parallel.

[0124] Hereinafter, examples related to the electrode disclosed herein will be described, but it is not intended that the technology disclosed herein be limited to the contents shown in these examples.

[0125] <Example 1>

[0126] Use the following positive electrode materials, Figure 1 The process shown is used to produce electrodes for non-aqueous electrolyte secondary batteries.

[0127] First, as a positive electrode active material, an average particle size (D 50 ) is 20 μm lithium transition metal oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) and carbon nanotubes (CNTs) with an oil absorption of 280 ml / 100 g were prepared as a conductive material. The mass ratio of the positive electrode active material to the CNTs was adjusted to 90:10.

[0128] As a non-aqueous electrolyte, a non-aqueous electrolyte prepared by dissolving LiPF6 as a supporting salt at a concentration of 1 mol / L in a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 was prepared.

[0129] The carbon nanotubes and the non-aqueous electrolyte are put into a planetary mixer for mixing, so that the non-aqueous electrolyte is impregnated in the carbon nanotubes. At this time, the non-aqueous electrolyte is added in such a way that the solid content of the wet powder becomes 70% by mass. Then, the positive electrode active material is put into the mixture for mixing, thereby obtaining a wet mixture. The wet mixture is granulated using a roller mill to prepare a wet powder (positive electrode material).

[0130] Next, the obtained wet powder (positive electrode material) is supplied to the above-mentioned roll film forming device to form a positive electrode active material layer on the surface of a long sheet of positive electrode collector composed of aluminum foil prepared separately. The electrode active material layer composed of the wet powder is well transferred to the electrode collector, and no undesirable conditions such as peeling are observed. Thus, a positive electrode sheet having a positive electrode active material layer formed on a sheet of positive electrode collector is obtained.

[0131] <Comparative Example 1>

[0132] As a comparison object, a positive electrode composed of a positive electrode material using acetylene black as a conductive material was prepared. Specifically, as a positive electrode active material, an average particle size (D 50 ) is 20 μm lithium transition metal oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) and acetylene black (AB) as a conductive material were prepared, and the mass ratio of the positive electrode active material to AB was adjusted to be 90:10.

[0133] As a non-aqueous electrolyte, a non-aqueous electrolyte prepared by dissolving LiPF6 as a supporting salt at a concentration of 1 mol / L in a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 was prepared.

[0134] The acetylene black and the non-aqueous electrolyte are put into a planetary mixer and mixed, so that the non-aqueous electrolyte is impregnated with the acetylene black. At this time, the non-aqueous electrolyte is added in such a way that the solid content of the wet powder becomes 70% by mass. Furthermore, the positive electrode active material is put in and mixed to obtain a mixture in a wet state. The mixture in the wet state is granulated using a roller mill to prepare the wet powder (positive electrode material) of this embodiment.

[0135] Next, the obtained wet powder (positive electrode material) was supplied to the above-mentioned film forming device, and an attempt was made to form a positive electrode active material layer on the surface of a separately prepared long sheet of positive electrode collector made of aluminum foil, but the positive electrode active material layer could not be formed on the positive electrode collector.

[0136] In summary, according to the electrode manufacturing method disclosed herein, an electrode is formed by granulating a wet powder formed by agglomerated particles containing at least an electrode active material, carbon nanotubes and a non-aqueous electrolyte and supplying an electrode active material layer composed of the wet powder to an electrode collector, thereby achieving the goal of suppressing production costs and manufacturing an electrode that does not substantially contain a binder resin and has an improved electrode density.

[0137] The specific examples of the present invention have been described in detail above, but these are only examples and do not limit the scope of the claims. The technology described in the scope of the claims includes various modifications and changes to the specific examples described above.

Claims

1. A method for producing an electrode for a non-aqueous electrolyte secondary battery, wherein the electrode comprises an electrode current collector of either a positive electrode or a negative electrode and an electrode active material layer, The manufacturing method comprises the following steps: a step of granulating a wet powder composed of aggregated particles containing at least an electrode active material, carbon nanotubes and a non-aqueous electrolyte, and The step of supplying an electrode active material layer composed of the wet powder onto the electrode collector to form an electrode; The granulation process includes the following treatments: a first mixing process of mixing the carbon nanotubes with the nonaqueous electrolyte so that the carbon nanotubes are impregnated with the nonaqueous electrolyte, a second mixing process of mixing the carbon nanotubes impregnated with the non-aqueous electrolyte with the electrode active material, The mixture obtained through the first and second mixing processes is subjected to a compression process.

2. The method for manufacturing an electrode according to claim 1, wherein: In the wet powder granulated in the granulation step, in the agglomerated particles, the solid phase and the liquid phase form a capillary state, When the entire wet powder is taken as 100 mass %, the solid content is 70 mass % or more.

3. The method for manufacturing an electrode according to claim 1 or 2, wherein: The oil absorption of the carbon nanotubes is 280 mL / 100 g to 1000 mL / 100 g.

4. The method for producing an electrode according to any one of claims 1 to 3, wherein: The electrode forming process forms the electrode by making the wet powder supplied between the first roller and the second roller adhere to the outer peripheral surface of the second roller as the electrode active material layer, and transferring the electrode active material layer from the outer peripheral surface of the second roller to the surface of the electrode collector supplied separately to the second roller, wherein the second roller is arranged opposite to the first roller.

5. A wet powder for forming an electrode active material layer on an electrode collector of either a positive electrode or a negative electrode, The wet powder is in powder form, The wet powder is composed of agglomerated particles including an electrode active material, carbon nanotubes and a non-aqueous electrolyte. When the whole wet powder is taken as 100 mass %, the solid content is 70 mass % or more. In the agglomerated particles, the solid phase and the liquid phase form a capillary state. The oil absorption of the carbon nanotubes is 280 mL / 100 g to 1000 mL / 100 g.

Citation Information

Patent Citations

  • Wet powder deposition method and wet granulation object

    JP2018113113A

  • Nonaqueous electrolytic secondary battery

    JP1995296794A

  • Method for producing nonaqueous electrolyte secondary battery

    JP2017117582A

  • Positive electrode active material slurry for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery

    JP2021015776A